Excesso de peso, nível de atividade física e atividades sedentárias em estudantes do ensino fundamental - Barros, Diego Silvestre de (2010)
Overweight and obesity is highlighted in the epidemiological scenario, not only because of its prevalence increased, but mainly because it is associated with a series of injuries and health problems. Data released by the World Health Organization - WHO in 2009 suggest that the prevalence of overweight and obesity so is increasing at an alarming rate, both in developed and in developing countries. Therefore, the objective of this study was to identify the prevalence of overweight in adolescents and its relationship with sedentary activities (TV and computer time and / or video game) and physical activity level. We conducted a crosssectional study with students from 5 th to 8 th of a degree of all municipal schools in Bauru. It was evaluated sedentary activities (TV and computer time and / or video game), level of physical activity among students and subscapular and triceps skinfolds. The analysis was performed using a descriptive approach and other analytical. In the descriptive approach was the distribution of absolute and relative frequency for categorical variables and the analytical approach was performed a bivariate analysis. As for the PAQ-C (physical activity questionnaire adapted for the age of the students), it was noted that 36.3% female and 26.3% of males are sedentary. Considering the triceps and subscapularis, it was noted that 12.4% and 12.0% respectively of the total number of students were overweight, as the use of computers,it was noted that 81.3% are in the habit using the computer and, say those 57% use computers frequently than 5 times per week and 29.1% with duration of 5 or more hours per day. The association between skin folds and the variables studied showed a statistically significant risk factors: hours and hours on television on the computer. It was concluded that an association exists between the vocal and sedentary activities, being appointed time spent in sedentary activities as an important factor in the development of overweight.